THE EXTENT OF LATE PLEISTOCENE GLACIATIONS IN THE ALTAI AND KHANGAI MOUNTAINS - Lehmkuhl F.; Stauch G.; Klinge M. (My University, 2004)
The current state of research concerning the extent of Late Pleistocene glaciations in Mongolia and the Russian Altai is summarised. Pleistocene moraines resulting from valley glaciers, plateau glaciers, cirque glaciers and ice streams can be found. The most extensive Late Pleistocene glaciation occurred in the western part of the Altai. However, the extent of Late Pleistocene ice in the Russian Altai is still under debate. In the eastern Altai and especially in the northern part of the Mongolian Altai, Pleistocene glaciers were restricted to several isolated mountain systems. To show the variations in the ice extent, the modern and Late Pleistocene equilibrium-line altitudes (ELAs) and the glaciated area are presented in two cross-sections through the Altai and Western Mongolia. The ELAs are relatively low in the more humid outermost ranges of the arid and semi-arid regions of Central Asia and rise towards the central part of Mongolia. The limited extent of present and Pleistocene glaciers in the eastern part of the Russian Altai and in the Mongolian Altai is the result of decreasing precipitation from west to east. This results in a rise of both the present-day and Pleistocene ELAs towards the east. However, it was more pronounced during the Pleistocene than today. There is an essential lack of absolute dating of glacial sediments in this particular region. Nevertheless, on the basis of present knowledge, most Late Pleistocene glacier advances in Mongolia and in the Russian Altai took place during Marine Isotope Stages (MIS) 2 and 4.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен